Silent Pandemic - Mojca Kukanja Gabrijelčič; Doroteja Zavšek (Annales, Series Historia et Sociologia)
Peer sexual violence is a complex phenomenon that encompasses unwanted sexual behaviour between individuals of the same age or in the same social environment. Using qualitative and quantitative research, we found out what is known about sexual violence, the frequency and factors of occurrence, and preventive (educational) approaches to prevent and cure signs of sexual violence among high school students. We also interviewed students who go to school and live in the vast area of Slovenian Istria, as we are interested in their opinion about the occurrence of sexual violence among their peers in this area. The results show that high school students (re)recognize situations of sexual violence very well.